2015
DOI: 10.1039/c5tc03116h
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of red to near-infrared emission in Mn2+ single doped magnesium zinc phosphate solid-solution phosphors by modification of the crystal field

Abstract: The different Mg/Zn ratios of (Mg1−xZnx)2.97(PO4)2:0.03Mn2+ result in various PL intensities and spectra profiles, which are related to the crystal field strength and local environment of the Mn2+ ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Herein, a dual-wavelength (530/650 nm) emitting material, Li 2 ZnSiO 4 :Mn 2+ , is produced by controlling the doping concentration of Mn 2+ , wherein the two emission bands have different concentration- and temperature-dependent luminescence behaviour, but exhibit quite similar excitation spectra. Although dual-emission characteristics have also been observed in two Mn 2+ -doped crystallographic sites in some cases, the two emission bands always show distinct excitation spectra in these systems 33 – 36 . Additionally, rational control of the site preference of the dopant is difficult in these cases.…”
Section: Introductionmentioning
confidence: 96%
“…Herein, a dual-wavelength (530/650 nm) emitting material, Li 2 ZnSiO 4 :Mn 2+ , is produced by controlling the doping concentration of Mn 2+ , wherein the two emission bands have different concentration- and temperature-dependent luminescence behaviour, but exhibit quite similar excitation spectra. Although dual-emission characteristics have also been observed in two Mn 2+ -doped crystallographic sites in some cases, the two emission bands always show distinct excitation spectra in these systems 33 – 36 . Additionally, rational control of the site preference of the dopant is difficult in these cases.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, because of the specific driving forces of Mn 2+ precipitation and site‐preference in a given host lattice, the practical realization of dual‐ or multiband emission from Mn 2+ ions is rather difficult. Even though dual‐band emission from Mn 2+ ions has been realized in some systems, the two emission bands possess distinct excitation spectra, thus, practical application remains limited …”
Section: Introductionmentioning
confidence: 99%
“…93 Ma et al reported that a series of novel red-to NIR-emitting Mn 2+ -activated (Mg 1−x Zn x ) 2.97 (PO 4 ) 2 (x = 0, 0.2, 0.4, 0.5, 0.6, and 0.8). 94 The fiveand six-coordinated structure for Mn 2+ enables the generation of NIR emission (peaking at 730 nm, lower energy) and red emission (peaking at 630 nm, higher energy). The main reason is that Mn 2+ ions are distributed at distinct crystal field environments with a different coordination.…”
Section: High-throughput Calculation and Crystal Structure Design To ...mentioning
confidence: 99%
“…(c) Normalized photoluminescence emission spectra of Li 2 Zn 1– x Mg x Ge 3 O 8 :3%Mn 2+ (0 ≤ x ≤ 0.9) . (d) Normalized photoluminescence emission spectra of (Mg 1– x Zn x ) 2.97 (PO 4 ) 2 :0.03Mn 2+ ( x = 0–0.8) under 417 nm excitation . Part b was reproduced with permissions from ref .…”
Section: High-throughput Calculation and Crystal Structure Design To ...mentioning
confidence: 99%